Gestión del Capital Intelectual en las Organizaciones - Pulgarín-Fernández, Celia María; Ormaza-Andrade, Jorge Edwin; Erazo-Álvarez, Juan Carlos (Revista Arbitrada Interdisciplinaria Koinonía, 2020)
The objective of the research is to analyze the management of intellectual capital in the business organization of the José Carrasco Arteaga hospital, located in Cuenca - Ecuador. Methodologically, the research was of a descriptive, non-experimental field type, working with a total sample of 324 individuals. The management of intellectual capital in the institution was established that 49% think that, if there is management of intellectual capital, while 24% do not consider that there is management of capital, while lower percentages are between sometimes there is management with 18% and 9% of respondents. The José Carrasco Arteaga specialty hospital could unify some departments into one and in this way optimize resources; In the same way, technological systems, both those that already exist and the implementation of new systems, help to reduce waiting times for patients, and optimize staff time and work.